STUDI TENTANG KEBUTUHAN PENGETAHUAN DAN KETERAMPILAN KHUSUS PERSONIL DALAM BIDANG PENERBANGAN DI INDONESIA - Yaddy Supriyadi; Rusdi Abdullah (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
Mitigation action towards aviation occurrence in Indonesia, according to National Transport Safety Commitee, have not been showing a significant results. It can be caused by, either the continuous development of aviation technology or the gaps between skills acquired during training phases and those required in the working environment. The TRAINAIR PLUS Training Development – Preliminary study will not only identify problems and the causes but also other potential problems that may arise in the future. The lack of understanding on separation, minimum English speaking skills, and no training on RNAV and RNP are findings related to training solution. Whilst the malfunction of communication devices, and no callibration are related to non-training solution